Comparison of Germ Patterns between Cholesteatom Tissue and Tympanic Cavum Mucosa Tissue in COSM with Cholesteatom at Dr. Mohammad Hoesin Hospital, Palembang - Resti Ramdani; Abla Ghanie; Fiona Widyasari; Ahmad Hifni; Irfannuddin Irfannuddin (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Chronic Suppurative Otitis Media (CSOM) is middle ear inflammation due to infection characterized by otorrhea through perforation of the tympanic membrane that occurs for more than three months. Identifying bacterial patterns in CSOM is essential for managing CSOM patients with cholesteatoma. Proper administration of antibiotics is crucial to overcome infection and prevent widespread resistance. To compare the germ patterns between cholesteatoma tissue and tympanic cavum mucosal tissue in CSOM patients with cholesteatoma. This observational study has a cross-sectional design, and data collection was carried out using primary data taken from 27 CSOM patients with cholesteatoma who underwent mastoidectomy surgery with a total of 54 research samples taken from the examination of cholesteatoma tissue swabs and tympanic cavum mucosal tissue from August to October 2023. From the reliability coefficient between the two tissues using the Cohen's Kappa technique, there is a significant concordance in the germ pattern between the tympanic cavum mucosa tissue and the tympanic cavum mucosa of 0.580 (Moderate) p<0.005, with Pseudomonas aeruginosa, Proteus mirabilis and Klebsiella pneumoniae with a significance value of 0.656 (Good) p<0.001. There is a significant concordance in the germ pattern between cholesteatoma tissue and tympanic cavum mucosa tissue in CSOM cases with cholesteatoma. The most common bacteria in both tissues are Gram-negative, namely Pseudomonas aeruginosa, proteus mirabilis, and Klebsiella pneumoniae.